모듈형 멀티레벨 컨버터의 신뢰성 디자인을 위한 IGBT 모듈 접합부 온도 기반 모의실험장치 - 조승래 (The Graduate School, Ajou University, 2020)
This thesis presents temperature-based simulator of insulated gate bipolar transistor (IGBT) modules for reliability design in modular multilevel converters (MMCs). The MMC is composed of various components, and the IGBT is the main component determining the reliability of the MMC. The failure of IGBTs is mostly due to the junction-temperature swings; thus, the thermal profile of the IGBT should be established to predict the lifetime. The thermal behavior depends on the current flowing to the IGBT, and the load-current profile is related to the application. In order to establish the thermal profile of the IGBT, the proposed hardware simulator provides various output currents while the junction temperature is measured simultaneously. In addition, a controller design is presented for simulation of the arm current, which includes a direct current (DC) component as well as an alternative current (AC) component with a fundamental frequency. The validity and performance of the proposed hardware simulator and its control methods are analyzed by various experimental results.
학위논문(석사)--아주대학교 일반대학원 :전자공학과,2020. 2
Keywords: IGBT 모듈; 모듈형 멀티레벨 컨버터; 모의실험장치; 신뢰성; 암전류; 온도 프로파일; 접합부 온도 측정